Exploring the built environment and physical activity in rural Ontario health units - Coghill, Cara-Lee M. (My University, 2013)
The purpose of this thesis was to explore how health units servicing large rural populations in Ontario are integrating the built environment into public health interventions related to physical activity for the purpose of fostering healthy and sustainable communities. Additionally, this research sought to identify barriers and/or enabling structures that rural health units face in addressing the built environment within physical activity programming.
This exploratory research study employed a descriptive qualitative approach. Semi-structured interviews were conducted with a purposeful sample of public health practitioners and managers identified by participating health units (n=12) as those most knowledgeable about program planning, implementation, and policy development in relation to physical activity and the built environment. Key themes were identified using qualitative content analysis and an inductive approach.
The types of interventions were: engagement with policy work at a county or municipal level; building and working with community partners; gathering and providing evidence; hosting knowledge sharing opportunities; program development and implementation; social marketing, information sharing and awareness raising; and resource development and dissemination. Barriers and enabling processes and structures were identified at an organizational, community, and systemic level. Specific rural contextual enablers and barriers were also identified.
This was the first study to the researchers’ knowledge that has examined current practices of Ontario’s rural health units related to built environment initiatives. In-depth perspectives elicited from public health practitioners and managers address gaps in the literature and contributes to new knowledge regarding built environment interventions to enhance physical activity in rural settings.
Keywords: built environment; physical activity; rural; public health; obesity; chronic disease prevention; Environmental Public Health; Public Health and Community Nursing; Public Health Education and Promotion; Environmental Public Health